Development of Oat Husk-Derived Nano-Silica for High-Performance and Sustainable Mortar Applications - Alvansazyazdi, Mohammadfarid; Carlosama Carde, Alvaro Yerandi; Rosillo Pilamunga, Jorge David; Bonilla Valladares, Pablo Mauricio; Patrice Martial, Debut Alexis; Santamaria Carrera, Jorge Luis; Cadena Perugachi, Hugo Alexander; Logacho Morales, Andrea Estefania; Tapia Vargas, Jhon Fabricio (INGENIO, 2025)
This study investigates the incorporation of nano-silica synthesized from agro-industrial waste—specifically oat husks—into plastering mortars. Amorphous silica is extracted through chemical treatment and converted into nano-silica via a sol-gel process, yielding 2.79%. Characterization through EDS, SEM, TEM, and XRD confirms nanoscale silica formation. Mortars are formulated using Atena Máster type N cement and fine aggregates from the “Copeta” quarry, verified under NTE INEN 2 536 standards. Nano-silica is added at dosages of 0.25%, 0.50%, 0.75%, and 1.00% by cement weight. The mixtures are evaluated in both fresh and hardened states. Fresh-state tests assess workability and flow, while compressive strength is measured at 7, 14, and 28 days. Results show that 0.25% nano-silica provides optimal performance, achieving 12.6 MPa at 28 days. Higher dosages lead to strength reduction, indicating a performance threshold. A cost-benefit analysis highlights the economic and environmental viability of converting agro-waste into high-performance materials. The findings underline nano-silica’s potential to enhance mechanical properties while promoting sustainability. This research demonstrates that controlled use of nano-silica from waste sources offers an eco-friendly, efficient solution for improving plaster mortar in the construction industry.